Implementasi Nilai-Nilai Pendidikan Agama Islam dalam Kegiatan Ekstrakurikuler Hadrah di SMP Muhammadiyah 7 Wuluhan - Hikmah, Faiqotul; Nursyamsiyah, Siti; Putra, Dhian Wahana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2025)
Islamic Religious Education is an education that aims to building the personality of students with Islamic Values, such as faith, Aqidah, and good morals. Hadrah instructors have an important role to educate, guide and provide examples to students to implement these Islamic values in everyday life. The research method used by the researcher is a qualitative approach, data obtained by the researcher through observation, in-depth interviews and document analysis. The result of the study indicate that the role of hadrah instructors at SMP Muhammadiyah 7 Wuluhan is very important in the formation of religious character of students. Hadrah instructors convey the values of Islamic Religious Education to students in an interesting and creative way, and provide exemplary examples through hadrah poetry. Guidance and motivation from hadrah instructors provide enthusiasm for students to develop their creativity, so that they can channel their interest and talents well. However, environmental factors from both the family and social environment also influence the success of this process, synergy between education at school, family support, and the social environment is needed to achieve optimal desired results in the formation of religious character of students.